Delivery of Marker‐Free DNA to Plant Genome by the Transgenic Selection‐Associated Fragment Elimination (T‐SAFE) System - Yi Yang; Huan Chang; Leiwen Pan; Dongbei Guo; Shun Peng; Ting Mao; Yuehui Zhang; Shui Wang (Plant Direct, 2025)
ABSTRACT The presence of a selection marker in transgenic plants has raised public concerns regarding health safety. We have developed a CRISPR/Cas9‐based DNA delivery system termed transgenic selection‐associated fragment elimination (T‐SAFE). The T‐SAFE system comprises four cassettes: the selection marker, CRISPR/Cas9, spacer‐plus‐protospacer adjacent motif (SP), and the cargo. The first two cassettes, the selection marker and CRISPR/Cas9, are collectively referred to as SCC. The SCC is flanked by two identical SPs derived from the fruit fly Ebony gene, which efficiently facilitate the SCC cleavage and subsequently lead to self‐elimination of the selection marker upon integration of exogenous DNA into the plant genome. To inhibit the production of a functional Cas9 protein in bacteria, the IV2 intron of the potato ST‐LS1 gene has been incorporated into the Cas9 gene. Additionally, the Cas9 gene is driven by a reproductive cell‐specific or inducible promoter to avoid SCC cleavage in nonreproductive plant cells. These innovative features allow the T‐SAFE system to achieve an elimination efficiency of the selection marker ranging from 10%–30% in Arabidopsis and 5%–8% in rice, with a DNA delivery capacity of approximately 10 kb. This approach offers a safe means for genetically modifying plants.